Antioxidant Activity of DPPH and ABTS Methods, from Jackfruit Leaf Extract and Fraction (Artocarpus heterophyllus) with ELISA Reader - Subekti, Istiara; Sujono, Tanti Azizah; Suhendi, Andi (Universitas Muhammadiyah Surakarta, 2025)
Oxidative stress caused by the accumulation of free radicals is a key factor in the development of degenerative diseases. Jackfruit leaves (Artocarpus heterophyllus), which are rich in polyphenolic compounds, have the potential as natural antioxidants. This study aims to activate the antioxidant activity of jackfruit leaf extracts and fractions. The study was conducted by extraction using the maceration method with 70% ethanol solvent and fractionated by vacuum liquid chromatography into polar, semi-polar and non-polar fractions. Antioxidant activity was measured in vitro, using 3 methods including DPPH, ABTS and FRAP which were read with an ELISA Reader with vitamin C as the reference standard. The results showed that the crude extract had strong antioxidant activity with an IC₅₀ value of 31.93 µg/mL (DPPH) and 29.59 µg/mL (ABTS), as well as the highest antioxidant equivalent ascorbic acid (AEAC) levels in the FRAP test. The polar fraction showed moderate antioxidant activity, while the semi-polar and non-polar fractions showed weak activity. These findings suggest that polar compounds such as flavonoids and phenolics play a role in the antioxidant effects of jackfruit leaves. In conclusion, jackfruit leaf extract and its polar fractions have significant antioxidant activity and show promise for further development as natural antioxidant agents in nutraceutical formulations aimed at preventing oxidative stress-related diseases.